ASP.NET MVC framework unleashed - Walther, Stephen (Sams, 2009)
In this book, world-renowned ASP.NET expert and member of the Microsoft ASP.NET team Stephen Walther shows experienced developers how to use Microsoft's new ASP.NET MVC Framework to build web applications that are more powerful, flexible, testable, manageable, scalable, and extensible. Writing for professional programmers, Walther explains the crucial concepts that make the Model-View-Controller (MVC) development paradigm work so well and shows exactly how to apply them with the ASP.NET MVC Framework. From controllers and actions to views and models, Walther demonstrates how to apply each ASP.NET MVC Framework feature in real-world projects. In Part II, you'll walk step-by-step through building a full-fledged ASP.NET MVC blog application that implements capabilities ranging from data access to validation. Through this case study, you'll learn how to build ASP.NET MVC applications using test-driven development processes that enable rapid feedback, greater productivity, and better quality. Throughout, Walther presents extensive code examples, reflecting his unsurpassed experience as an ASP.NET instructor, a leading commercial developer, and now as a member of Microsoft's ASP.NET development team. Understand how to: Build enterprise-scale web applications far more rapidly and effectively Develop web applications that are easier to maintain and extend over time Gain unprecedented control over the appearance of your website or application Expose intuitive URLs that are friendlier to search engines and users alike Create ASP.NET MVC models that contain all your application's business, validation, and data access logic Make the most of HTML helpers, model binders, action filters, routing, and authentication Efficiently deploy your ASP.NET MVC applications Use the lightweight JQuery JavaScript library to easily find and manipulate HTML elements Create ASP.NET MVC applications using unit test and mock object framework.